The Correlation of Nutrition Knowledge and Nutrition Label Use Among Adolescents in Semarang City, Indonesia - Nita Prameswari, Galuh; Desy Putriningtyas, Natalia; Nugroho, Efa; Rahmat Kurnia, Arif (Journal of Health Education, 2024)
Background: Nutrition label is part of public health nutrition intervention, but it seldom studied in Indonesia. It is essential to measure the relationship between nutrition labels and nutrition knowledge to understand its impact, especially among adolescents. Peers and social life encourage adolescents to choose specific actions, including food and drink, which affects their nutrition status. Methods: This study used a cross-sectional design on 404 respondents in Semarang City. The instrument used was the Comprehensive General Nutrition and Nutrition Label Questionnaire (CGN2LQ). Data analysis includes univariate analysis and bivariate analysis. The statistical test used is the correlation test to determine the correlation between nutrition knowledge and nutrition label use for adolescents in Semarang City. The analysis showed a significant relationship between nutrition knowledge and nutrition label use (p<0.05). Results: The direction of the correlation is positive or unidirectional, meaning that the higher the nutrition knowledge of adolescents, the higher the use of nutrition labels on packaged products. The test results showed that the strength of the correlation was weak (r=0.333). The significant correlation but weak strength means that the correlation was statistically significant but not practically relevant. Conclusions: There is a need to increase the knowledge of nutrition in the adolescent age group to improve the habit of using nutrition labels on packaged products to determine the choice of packaged food and beverage consumed.